Evaluation of general dentist's and dental student's knowledge about emergency management of dentoalveolar trauma in Bojnurd, North Khorasan, Iran - Dastpak Mahsa; Masoumi Fateme; Norozi Khalili Mina; Rajaey Amir (Wolters Kluwer Medknow Publications, 2022)
Background: Traumatic dental injuries (TDIs) are one of the most common dental problems among children and adolescents, which usually occur in the anterior parts of the mouth and have great impact on the patient's physical and mental health. Therefore, dentist's knowledge and effective measures in the treatment of TDI are the most important factors in improving the prognosis of these teeth. Aims: The aim of this study was to evaluate the knowledge of general dentists working in Bojnurd and also 6th-year dental students about the treatment of such injuries. Materials and Methods: In this cross-sectional study, a questionnaire was provided to 70 general dentists and 6th-year dental students, including personal information and questions related to the knowledge of general dentists, on how to deal with various TDIs by available methods. Data were analyzed using t-test, Chi-square test, Kruskal-Wallis test, and analysis of variance, Spearman's, and Pearson's correlation coefficient. Results: Regarding general dentists' knowledge about dentoalveolar trauma: 39 (55.7%) were moderate, 28 (40%) were good, and 3 (4.3%) were excellent. The mean value knowledge of dentists and dental students was 8.18 ± 1.98. There was no significant relationship between age, gender, place of work, university of study, desire for education, and self-evaluation of dentists and level of awareness (P = 0.26, P = 0.61, P = 0.47, P = 0.93, P = 0.35, and P = 0.57, respectively). Conclusions: The results of our study indicate that majority of the participants are moderately aware of TDIs and the type of treatment, and due to the increasing prevalence of dental trauma and its high complications, especially in children, the need to make appropriate plans to update the level of knowledge of general dentists in the management and treatment of TDI increases.